"Living High-Training Low" improved weight loss and glucagon-like peptide-1 level in a 4-week weight loss program in adolescents with obesity: A pilot study. Issue 8 (February 2018) - Yang, Qin; Huang, Guoyuan; Tian, Qianqian; Liu, Wei; Sun, Xiangdong; Li, Na; Sun, Shunli; Zhou, Tang; Wu, Nana; Wei, Yuqin; Chen, Peijie; Wang, Ru
Abstract: Background: "Living High-Training Low" (LHTL) is effective for the improvement of athletic ability; however, little is known about the effect of LHTL on obese individuals. The present study determined whether LHTL would have favorable influence on body composition, rebalance the appetite hormones, and explore the underlying mechanism. Methods: Adolescents with obesity [body mass index (BMI) >30 kg/m 2 ] were randomly assigned to "Living Low-Training Low" (LLTL, n = 19) group that slept in a normobaric normoxia condition and the LHTL (n = 16) group slept in a normobaric hypoxia room (14.7% PO2 ∼2700 m). Both groups underwent the same aerobic exercise training program. Morphological, blood lipids, and appetite hormones were measured and assessed. Results: After the intervention, the body composition improved in both groups, whereas reductions in body weight (BW), BMI, and lean body mass increased significantly in the LHTL group (all, P  < .05). In the LLTL group, cholecystokinin (CCK) decreased remarkably ( P  < .05) and CCK changes were positively associated with changes in BW ( r  = 0.585, P  = .011) and BMI ( r  = 0.587, P  = .010). However, in the LHTL group, changes in plasma glucagon-like peptide-1 (GLP-1) and interleukin-6 (IL-6) levels, positively correlated with each other ( r  = 0.708, P  = .015) but negatively with BW changes ( r  = −0.608, P  = .027 and r  = −0.518, P  = .048, respectively). Conclusion: The results indicated that LHTL could induce more weight loss safely and efficiently as compared to LLTL and increase the plasma GLP-1 levels that may be mediated by IL-6 to rebalance the appetite. Thus, an efficient method to treat obesity and prevent weight regain by appetite rebalance in hypoxia condition was established.